Creating Authentic Cultural Experiences in Finland - Pulliainen, Aino (2021)
The aim of this thesis was to explore the importance of authenticity in experiences that involve cultural aspects. The thesis focused on Finland and the indigenous cultural groups that are present in the area, including Sami people and Karelians. The author conducted a qualitative research on the topic to collect more relevant and real information directly from the people who represent these cultural groups. The goal was to gain a deeper understanding of these cultures and the effects of hospitality and experience industry on them. Through this study, the author wanted to shed more light to the indigenous groups in Finland. The author explored the effects of hospitality and experience industry and how to provide authentic experiences that include cultural aspects, while remaining respectful and considerate. The outcome of this research thesis provided useful information and advice for the industry. The approach of the study was to start of with a desk study, which included literature research. From there, the author built their own framework and collected the needed sources. The research helped her to build a base of the important issues and questions for the research, which will later be crucial during the qualitative research interviews. Interviews were conducted as semi-structured, one-on-one interviews. There were 8 respondents. The literature research showed, that there are three identified cultural groups in Finland, those list Sami people, Karelians and Finns. Finns being the majority group, therfore not main focus of the research. All of these groups have different and unique aspects to them. There were also some issues found, since opinions can vary especially about Karelia. Source criticism needed to be practised. The author has asked opinions of individuals who are from these cultural groups in question, to suggest the most reliable sources for reading materials to get the best and deepest understanding of the topic. So that she could avoid hearing the stories and history from someone elses perspective. The author researched the importance of authenticity in the industry, how to provide cultural experiences, maintaining the culture and experience industry as a whole. The outcome of the research supported the literature study. In this industry, we need to involve, hear and really listen to the indigenous communities, because our actions in the experience and hospitality field can really affect the preservation of these cultures. Harvard referencing was used in this thesis.